"Percepción de factores de riesgo laboral y conductas protectoras en el personal de Enfermería del Hospital La Esperanza" - Paez Escobedo, Katherinne Lisset (2015)
This research study is correlational descriptive, was held in Trujillo, in order to identify whether there is a relationship between perception of occupational risk and protective behaviors of occupational health nursing team working in the Hospital La Esperanza, it was conducted during the months of July to September 2013. The sample universe consisted of eight nurses and four nursing technicians, a total of 12 workers of Hope Hospital; data were automatically processed using statistical analysis system through the test Chi square independence criteria, the results reported that 66.7 does not receive occupational risk factors and 41.7 percent being applied bad protective behaviors. Chi-square value of 10,375 with probability 0.035 is observed to be significant, so no relationship between perception of occupational risk factors and protective behaviors occupational health nurses who work in the Hospital La Esperanza.